Dealing With Isolation Using Online Morning Huddles for University Lecturers During Physical Distancing by COVID-19: Field Notes - Kotera, Yasuhiro; Green, Pauline; Rhodes, Christine; Williams, Alan; Chircop, James; Spink, Rachel; Rawson, Rebecca; Okere, Uche (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2020)
Isolation can affect our well-being negatively. To prevent the spread of the infection COVID-19, many workers, including university lecturers, are required to work from home. In order to maintain high levels of well-being and team cohesion, academics at the University of Derby Online Learning initiated a virtual huddle to briefly socialise and check on their colleagues’ well-being every morning. This piece of field notes reports the context (COVID-19 in the United Kingdom), the details of this morning socialization, the first-hand experience of attending this huddle, and possible applications. Perceived positive impacts of our huddles include better well-being, cultivating compassion in team culture, and enhanced team cohesion. These advantages can be also useful in student supervision, wider socialization with colleagues to counter the silo mentality, and other occupational sectors. Our field notes will be helpful for lecturers and other types of employees who work collaboratively yet in isolation during this uncertain and challenging time of crisis.